The Relationship Between Employee Engagement, Physical Wellness, Work-Life Balance and Employee Well-Being - Abg Abdullah, Dayang Nailul Munna; Zakaria, Ridhawati; Dahalan, Noor Azura; Kamarul Zaman, Maliza Delima; Ishak, Zully Afiqah (Information Management and Business Review, 2024)
Employees often face challenges in finding work environments that consistently promote their well-being, despite spending a significant portion of their lives at work. This research investigates how employee engagement, work-life balance, and physical wellness relate to employee well-being at Nabati Food Malaysia Sdn. Bhd. Using a quantitative approach, the study tested three hypotheses through a survey with 187 participants, utilizing convenient sampling and an online questionnaire. Data were analyzed with the SPSS version 24.0. The results showed significant relationships between all variables and employee well-being, with employee engagement having the most substantial impact. The study recognized its limitations and provided recommendations for future research. Overall, the findings offer valuable insights for Nabati Food Malaysia and the fast-moving consumer goods sector, emphasizing the importance of enhancing employee well-being to improve business operations and employee satisfaction.